2010
DOI: 10.1167/iovs.09-3905
|View full text |Cite
|
Sign up to set email alerts
|

Refractive Power and Biometric Properties of the Nonhuman Primate Isolated Crystalline Lens

Abstract: Purpose. To characterize the age dependence of shape, refractive power, and refractive index of isolated lenses from nonhuman primates. Methods. Measurements were performed on ex vivo lenses from cynomolgus monkeys (cyno: n = 120; age, 2.7-14.3 years), rhesus monkeys (n = 61; age, 0.7-13.3 years), and hamadryas baboons (baboon: n = 16; age, 1.7-27.3 years). Lens thickness, diameter, and surface curvatures were measured with an optical comparator. Lens refractive power was measured with a custom optical system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 26 publications
8
15
0
Order By: Relevance
“…Studies in in vitro-human crystalline lenses 58 reported a positive conic constant in the anterior surface and scattered values of approximately 0 for the posterior. The values of asphericity reported here for the fully accommodated state agrees well with those reported by a previous study in isolated cynomolgus monkey lenses, 33 where a wide range (from À6 to þ4) was reported. The high value of lens anterior surface asphericity in monkeys in the unaccommodated state, never reported in humans, may be due to the differences in size between the species, to the young age of the monkey lenses compared with the humans from prior literature, and to the larger accommodative range of monkey lenses (up to 30 D) in comparison with the human lens (no more than 10 D).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Studies in in vitro-human crystalline lenses 58 reported a positive conic constant in the anterior surface and scattered values of approximately 0 for the posterior. The values of asphericity reported here for the fully accommodated state agrees well with those reported by a previous study in isolated cynomolgus monkey lenses, 33 where a wide range (from À6 to þ4) was reported. The high value of lens anterior surface asphericity in monkeys in the unaccommodated state, never reported in humans, may be due to the differences in size between the species, to the young age of the monkey lenses compared with the humans from prior literature, and to the larger accommodative range of monkey lenses (up to 30 D) in comparison with the human lens (no more than 10 D).…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies have investigated the lens power change with accommodation, and the role of the GRIN in cynomolgus monkeys and hamadryas baboons, assuming a value for the outer cortex refractive index. 33,34 The relative contribution of the GRIN to lens power appears to remain constant with accommodation. 9,34,35 This suggests that a homogenous index material in lens refilling procedure would be equally efficient in producing a refractive power change (assuming identical lens shape changes) than the natural lens GRIN material.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…GABA genes were also responsible for the enrichment of ASCs in eye lens development loci. GABA signaling influences lens growth (Schwirtlich et al 2011), and the primate lens is known for its ability to accommodate an exceptionally wide range of focal lengths (Borja et al 2010). Thus, widespread anthropoid gain of function in the GABA signaling pathway could potentially have played a role in primate visual acuity.…”
Section: Discussion Molecular Origins Of Anthropoid Primatesmentioning
confidence: 99%